The Prognosis of ART Is Not Altered in Cystic Fibrosis Women: A Case-Report Study - Braham, Inès; Morisot, Adeline; Boukaïdi, Samir; Perceval, Marie; Durieu, Isabelle; Rousset-Jablonski, Christine; Hieronimus, Sylvie; Leroy, Sylvie; Chevalier, Nicolas (Frontiers in Endocrinology, 2022)
Research question: Unlike in men, a very limited number of studies were focused on the specificity of ART management of cystic fibrosis (CF) in women. The purpose of this study was to determine the causes of infertility in patients, the appropriate ART treatment and their prognosis in terms of pregnancy. Design: We conducted a multicentre analytical case-control study including CF women who were age-matched to non-CF women. We reported the causes of infertility, the ART management type and pregnancy outcomes. Results: 17 cases were compared to 34 controls. There was no significant difference between the groups concerning cause infertility. There was a non-statistically significant trend with a lower antral follicle count in CF compared to controls (19.5 versus 26.8, p=0.08). IUI seems to be as successful as IVF/ICSI in CF as opposed to controls where the IVF/ICSI is the most effective (in CF group for HCG >100: 38.8% vs. 36.8%, p=0.4175). There are more embryos obtained in CF than in controls (3.1 versus 1.6, p=0.02). The number of oocytes and embryos obtained and pregnancy outcomes remain similar between DF508 homozygous group and others CFTR mutations group. The mean FEV1 remains similar between women with or without ongoing pregnancy. Conclusion: In absence of any other pathology, IUI may be first option for CF women. If insemination fails, IVF with a low dose of gonadotropins may be more appropriate to prevent the risk of hyperstimulation syndrome. FEV1 and genetic do not seem to be contributing factors in the prognosis of ART.